PERUBAHAN FISIK BERHUBUNGAN DENGAN TINGKAT KECEMASAN WANITA PREMENOPAUSE DI DESA JAHARUN A KABUPATEN DELI SERDANG - Yuliana, Melisa; Hastuti, Yulina Dwi (Colostrum Jurnal Kebidanan, 2019)
Introductions : Along with the increasing life expectancy, there are many processes of development and growth found in human body. But the development and growth will stop at a certain stage, so many changes in the functioning of the human body will take place. During this period, physiological changes can arise which can lead to anxiety. Anxiety is often associated with anxiety in dealing with a situation that has never been experienced before. This study aims to determine the frequency distribution of physical changes and frequency of anxiety, and to determine the relationship between physical changes and anxiety of premenopause women. Methods : This study was an analytical study designed with a cross sectional design, carried out in March-May 2019. The study samples were 47 premenopause women aged 40-55 years in Jaharun A Village obtained through Purposive Sampling techniques from 90 populations. The data used in this study are primary data obtained from the questionnaires. The data obtained will be analyzed with univariate and bivariate analysis and tested with Chi Square test with a value of ? <? or significance level of 95% (? = 0.05). Results and Discussions: The results showed that there was a relationship between physical changes with anxiety levels of premenopause women with the Chi Square test results obtained ? = 0.018 Conclusions:This study concluded that there was a relationship between physical changes and anxiety levels in premenopause women. The Head of Jaharun A Village is expected to work with the Health Center to provide health education so that premenopause women are not anxious during the premenopausal period.